2022
DOI: 10.3390/ijerph192013700
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 8-Week β-Alanine Supplementation on CRP, IL-6, Body Composition, and Bio-Motor Abilities in Elite Male Basketball Players

Abstract: The purpose of this study was to evaluate the effect of 8-week β-alanine supplementation on C-Reactive Protein (CRP), interleukin-6 (IL-6), body composition, and bio-motor abilities in elite male basketball players. Twenty male basketball players (age: 23 + 0.6 years; body mass: 78.3 + 4.8 kg; height:185.3 + 5.4 cm, %BF, 15.2 ± 4.8) volunteered to participate in this study. They were divided into a β-alanine group (BG, N = 10) and a placebo group (PG, N = 10). All players were preparing for university competit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…The acute effect of a PWS (containing caffeine, β-alanine, creatine, citrulline malate and BCAAs) on agility performance in basketball players has never been examined. Caffeine [ 1 ] appears to be the primary reason for such an acute improvement since the other components employed in the present study’s PWS (for instance, creatine and β-alanine) seem to require a more extended administration period for significant effects to be observed [ 65 , 66 ]. Indeed, according to a recent meta-analysis, acute caffeine supplementation 60 min before exercise at a dosage of 3–6 mg per body mass induces significant, acute improvements in athletes’ agility performance [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…The acute effect of a PWS (containing caffeine, β-alanine, creatine, citrulline malate and BCAAs) on agility performance in basketball players has never been examined. Caffeine [ 1 ] appears to be the primary reason for such an acute improvement since the other components employed in the present study’s PWS (for instance, creatine and β-alanine) seem to require a more extended administration period for significant effects to be observed [ 65 , 66 ]. Indeed, according to a recent meta-analysis, acute caffeine supplementation 60 min before exercise at a dosage of 3–6 mg per body mass induces significant, acute improvements in athletes’ agility performance [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research by Turcu et al demonstrated that 8 weeks of Beta-Alanine supplementation reduced catabolic responses (CRP) and muscle damage indices (Lactate and CRP), and enhanced anaerobic peak power and performance (4). These findings suggest that Beta-Alanine's contribution to carnosine content modulates catabolic effects and enhances the performance of elite volleyball players (4).…”
Section: Introductionmentioning
confidence: 73%
“…Twenty-two male volleyball players from the Division 1 Volleyball League, aged 22 -28 years, were selected and randomly divided into two groups of 11 individuals: (1) A supplement group and (2) a control group. The supplement group received 6.4 g/day of Beta-Alanine in 8 servings of 800 mg each through oral administration for 4 weeks, while both groups continued their regular volleyball training three days a week (4,17), on even days. The control group engaged in the same training regimen but did not consume any supplements.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study showed that as athletic experience and sporting age increase, the components of autonomy improve, which we consider to have an important role in the optimization of sports performance in bodybuilding. Numerous studies on autonomy have been carried out to identify autonomy factors depending on the type of sport practiced [99][100][101], the gender of athletes [102], the manifestation of self-determination and motivation in recreational and competitive athletes [103,104], and the level of sports skills in champions [52,103]. Research on personal autonomy in athletes has also focused on identifying intrinsic and extrinsic motivations for practicing a certain type of sport and improving sports performance [105][106][107][108].…”
Section: Discussionmentioning
confidence: 99%